Coleção Desafios Das Engenharias: Engenharia Sanitária 2 2021
DOI: 10.22533/at.ed.37921131019
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Potencial De Utilização De Resíduo De Eta Como Impermeabilizante De Obras De Terra Para a Contenção De Resíduos

Abstract: Direitos para esta edição cedidos à Atena Editora pelos autores. Open access publication by Atena Editora Todo o conteúdo deste livro está licenciado sob uma Licença de Atribuição Creative Commons. Atribuição-Não-Comercial-NãoDerivativos 4.0 Internacional (CC BY-NC-ND 4.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…Compaction Normal Proctor was done, stating wopt = 86.0% and ρd,opt = 1.26 g/cm³ for WTS, indicating its high-water absorption capacity while also exposing high retention capacity, corroborating with several studies that found wopt higher than 100% and proved to be very difficult to compact WTS due to a formation of a very dense material block [28], [29]. In addition, a lower specific weight compared to the soil was exhibited.…”
Section: Geotechnical Characteristicssupporting
confidence: 80%
“…Compaction Normal Proctor was done, stating wopt = 86.0% and ρd,opt = 1.26 g/cm³ for WTS, indicating its high-water absorption capacity while also exposing high retention capacity, corroborating with several studies that found wopt higher than 100% and proved to be very difficult to compact WTS due to a formation of a very dense material block [28], [29]. In addition, a lower specific weight compared to the soil was exhibited.…”
Section: Geotechnical Characteristicssupporting
confidence: 80%